Infrared thermography as a modality for tracking cutaneous temperature change and post-mortem interval in the critical care setting. (October 2021) - Chan, Peter Y.; Tay, Andrew; Chen, David; Timms, Paddy; McNeil, John; Hopper, Ingrid
Abstract: Purpose: To evaluate the potential use of cutaneous facial temperature change as measured by an infrared camera as a marker of postmortem interval (PMI) in the minutes immediately following death. Methods: This was a prospective, observational pilot study using a convenience sample of all deaths which occurred in a room in an Intensive Care Unit equipped with a ceiling mounted thermal camera. Cutaneous temperature measurements were taken from 60 min antemortem to as long as possible postmortem. Results: A total of 134 separate measurements was taken from 5 patients, with 65 occurring antemortem, and 69 occurring post-mortem. The longest recorded post-mortem time was 130 min. A Kruskal-Wallis ANOVA testing the hypothesis that there was a difference in facial temperature at each of the different timepoints showed significance ( p  = 0.029). Post-Hoc comparisons were then performed to compare median temperature values at each timeframe to the baseline value. Compared to baseline, there was a significant difference in facial temperature at 30, 60, and 90 min ( p  = 0.007, p  = 0.01, p  = 0.016) (Table 2). Conclusion: There is a statistically significant cutaneous facial temperature change in patients immediately following death as measured by a thermal camera. There is potential for infrared thermography to identify changes immediately before and after death in environments where traditional temperature measurement cannot be accomplished. More work needs to be done to confirm whether a precise postmortem interval (PMI) could be derived from these values.